2021
DOI: 10.1119/5.0019320
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Students’ Values Through Role Play about Socioscientific Issues

Abstract: During the course of international curriculum reform, decision making about socioscientific issues (SSI)—open-ended controversial issues with connections to science, technology, and society—has been labeled a critical tool for achieving scientific literacy. Therefore, enhancing students’ socioscientific decision making as part of science education has become a pressing issue; global SSI affect people every day. This leads people worldwide to collaboratively involve in decision-making processes to solve these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…One reason for this is the combination of moral reasoning and argumentation processes. Individuals exposed to various points of view during argumentation processes may increase their socio-scientific responsibilities toward the issue (Namdar and Oğuz Namdar, 2021). Furthermore, research shows that people who are concerned about climate change engage in more climate-friendly behaviors, have more domain knowledge, and are more concerned (Kuthe et al, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One reason for this is the combination of moral reasoning and argumentation processes. Individuals exposed to various points of view during argumentation processes may increase their socio-scientific responsibilities toward the issue (Namdar and Oğuz Namdar, 2021). Furthermore, research shows that people who are concerned about climate change engage in more climate-friendly behaviors, have more domain knowledge, and are more concerned (Kuthe et al, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Socio-scientific issues (SSI) are complex, openended, and real-world topics that involve scientific, social, and ethical components. Previous work has shown that SSI-based classroom instruction advances students' critical reasoning, science literacy, and interest in the curricula (Namdar & Namdar 2021). Students in UK secondary schools using bioethics, physics, and ethics online modules found open-ended ethical dilemma questions and thought experiments unexpectedly rewarding (Green & Wishart, 2008).…”
Section: Why Use Medical Physics In the Physics Classroom?mentioning
confidence: 99%